PENGEMBANGAN SUMBER DAYA MANUSIA DALAM TEKNOLOGI INFORMASI, KOMUNIKASI, DAN PUBLIKASI TERHADAP PENINGKATAN PERTUMBUHAN EKONOMI KREATIF PADA PARIWISATA HALAL DI MADURA - Rahman, Mohammad Hasan; Wildan, Muhammad Alkirom (JURSIMA, 2022)
Halal tourism has become an important sector in the growth of the creative economy in Madura. In the current digital era, information, communication and publication technology play a key role in raising the profile of Madura's halal tourism and creating sustainable business opportunities. However, to take full advantage of this potential, it is necessary to pay attention to the development of quality human resources (HR) in this field. This research was conducted to investigate the impact of human resource development in information technology, communication and publications on the growth of the creative economy in the context of halal tourism in Madura. The research methods that will be used are surveys, interviews, and secondary data analysis to collect relevant data. It is hoped that the results of this research will provide in-depth insight into the importance of investment in human resource development that focuses on information and communication technology in the halal tourism sector. It is hoped that these findings can provide guidance for government, industry and educational institutions to design human resource development programs that have a positive impact on the growth of the creative economy in Madura. This research will provide an important contribution to our understanding of how human resource development in information, communication and publication technology can spur the growth of the creative economy in the context of halal tourism, which also has the potential to become a model for other regions wishing to utilize the creative economy in culture-based tourism.